Mengembalikan Senyum Porselen Anda: Panduan Perbaikan Intraoral untuk Gigi Tiruan Cekat Porcelain - Sarwono, Aditya Pratama; Emeralda, Maria Verena; Tandjaja, Cynthia (E-Prodenta Journal of Dentistry, 2024)
Background: Porcelain or ceramic-based materials are popular in dentistry due to their aesthetic appeal andbiocompatibility. However, chipping or fractures in fixed partial dentures can disrupt aesthetics and functionality.Intraoral repair offers a cost-effective and time-saving solution. Objective: This study aims to guidepractitioners in managing chipping crowns, saving time and costs while ensuring satisfactory outcomes forpatients. Method: The review included articles on intraoral repair of porcelain fixed partial dentures, publishedin peer-reviewed journals, available in English, and including clinical trials, case reports, and reviews. Exclusionswere non-dental studies, non-English articles, and studies focusing on temporary restorations. Data on theetiology of chipping, necessary tools, and management steps were collected. Result: Porcelain Fused to Metal(PFM) denture repairs are difficult due to color matching and procedural complexity. Repairing Lithium Disilicatedentures is moderately challenging, requiring meticulous surface preparation. The most complex repairs are forZirconia-based prostheses, needing specialized equipment and advanced techniques for a durable bond.Conclusion: Intraoral repair techniques provide a quick, precise, and comfortable solution for patients.Understanding the stages of intraoral repair allows clinicians to achieve optimal functional and aesthetic results.Clinicians should evaluate their expertise and resources to select the appropriate technique, with compositeresin repairs being the easiest and Zirconia-based repairs the most challenging. This method helps deliver quickand satisfying results, enhancing the longevity and aesthetics of fixed porcelain dentures.